An ontology-based semantic retrieval approach for heterogeneous 3D CAD models. Issue 4 (October 2016) - Qin, Feiwei; Gao, Shuming; Yang, Xiaoling; Li, Ming; Bai, Jing
Abstract: Many types of heterogeneous CAD models created by previous product development activities are stored in enterprise databases. Searching reusable CAD models for engineer design requirements is still very difficult. In this paper, we propose an ontology-based semantic retrieval approach for heterogeneous 3D CAD models by using semantic web theory and information retrieval theory. By exploiting layered feature ontology and ontology mapping, a uniform description for heterogeneous CAD models is generated as semantic descriptor. Meanwhile, to improve the representative ability, several heuristic rules are constructed with the aid of SWRL language and ontology reasoning is acted on the semantic descriptors, which makes our retrieval system achieve better performance. Furthermore, multi-mode similarity measurement is carried out to meet engineers' diversified requirements. We demonstrate the feasibility and effectiveness of our approach through experiments on heterogeneous 3D CAD model library.